Effects of soaking and steaming regimes on the quality of artisanal parboiled rice - Graham-Acquaah, S.; Manful, J.T.; Ndindeng, S.A.; Tchatcha, D.A. (Hindawi Limited, 2015)
The effects of initial soaking temperatures (IST) (30–90C) and steaming times (STM) (5–20 min) during artisanal parboiling on the quality of parboiled rice were studied. Total milling yield and head rice yields increased as IST increased. Water absorption of the rice kernels during parboiling increased as IST increased and correlated positively with head rice yield. Chalkiness decreased with increasing IST and this decrease was enhanced by increasing STM. Cooked parboiled rice had harder texture. While ISTs between 30 and 50C did not alter much the paste viscosities of parboiled samples, IST above 50C caused significant decreases in paste viscosities. Increasing STM caused steady decreases in paste viscosities at all ISTs. Soaking and steaming regimes affected the physicochemical properties of the parboiled rice and must be considered carefully in order to produce good quality artisanal parboiled rice that meets consumer needs and also to alter the functional properties of rice in food formulations.